The Malaysian Government’s Road Accident Death Reduction Target for Year 2010. - Law, Teik Hua; Radin Sohadi, Radin Umar; Wong, Shaw Voon (2005)

(untitled)
Objective: this paper makes a projection of the vehicle ownership rate to the year 2010 and to use this projection to predict road accident deaths in year 2010. the projection served as an indicator for the Malaysian government to achieve a 4 road accident deaths per 10,000 vehicles safety target in year 2010. Method: the study included the predication of vehicle ownership and the analysis of past trends in the road accident death rate. Gompertz growth model was used to project vehicle ownership and the prediction of road accident death rate was done using Autoregressive integrated Moving Average (ARIMA) model with transfer noise function. Results and Conclusions: the Gompertz model predicted that vehicle ownership would be equal to 0.4409 by the year 2010. the road accident death rate is projected to decrease to 4.22 in year 2010, at an average decline rate of 2.14% per annum. This result suggests that a minimum 2.18% reduction per annum is required to achieve the nation target in year 2010.